Health-Related Physical Fitness Test and Norms for Undergraduate Students, Faculty of Education Nakhon Ratchasima Rajabhat University - Siriwatthanasin, Duangjai; Jindasorn, Kridsana; Nunchan, Tanawan (Ratchaphruek Journal, 2025)
This research aimed to develop a test, establish norms-referenced standards, and study the results of the physical fitness test for health for undergraduate students at Nakhon Ratchasima Rajabhat University. The sample consisted of 300 first-to fourth-year students from 19 majors in the academic year 2022, using a multi-stage random sampling method. The experimental instrument comprised 7 items of health-related physical fitness tests: Body Mass Index (BMI), percent fat, sit-and-reach test, back scratch test, 7-stage sit-up test, curl-up test, and the PACER test. Data were analyzed using mean and standard deviation, and normative criteria were established based on measures of central tendency. The results of the health-related physical fitness test showed a content validity of 1.00, reliability of 1.00, 1.00, 0.92, 0.95, 0.99, 0.99, 0.83, and 0.87, respectively, and inter-rater reliability of 1.00. The normative standards for school norms health-related physical fitness tests are categorized into five-level and seven-level scales. The test results revealed that the BMI of male students was in the overweight range, while that of female students was within the normal range. Most students had test results at a moderate level. For the 7-stage sit-up test, male students were at a good level, while female students were at a moderate level.